Knowledge, Attitude, and Preventive Practice Regarding Dengue Fever among the High-risk Population in Nepal - Bhattarai, Jamuna; Thapa, Muna Rana; Gauro, Pooja; Adhikari, Sabina; Chaudhary, Sonam (International Journal of Applied Sciences and Biotechnology, 2024)
Introduction: Dengue, transmitted by Aedes mosquitoes, has been endemic in Nepal, especially in the tropical lowlands since 2004. This study examined Knowledge, Attitude, and Practice (KAP) levels regarding dengue fever among high-risk populations in Nepal's Terai lowlands. Method: A descriptive cross-sectional survey was conducted in specific wards of Biratnagar and Birgunj Metropolitan Cities. 280 purposively selected households were surveyed using a rigorously pre-tested KAP questionnaire, translated to ensure integrity. Data, collected from May to August 2018 through household interviews and inspections for mosquito breeding sites, was verified, cleaned, and analyzed with SPSS version 20, utilizing descriptive and inferential statistics to assess dengue prevention behaviors. Results: The survey in Biratnagar and Birgunj revealed moderate dengue prevention knowledge (mean score 54.20, SD 16.50) and variable practice scores (mean 66.80, SD 17.30). Positive attitudes were prevalent (87.9% in Biratnagar, 92.9% in Birgunj). Knowledge positively correlated with attitudes (0.324) and practices (0.318), while attitudes and practices also showed a positive correlation (0.356), highlighting the interdependence of these factors. Conclusion: The study highlights a positive association between knowledge, attitudes, and practices, indicating that improving one aspect can beneficially influence others. Despite moderate knowledge and practices, and positive attitudes among respondents, variability suggests a need for targeted interventions. The similarity in KAP levels between Biratnagar and Birgunj implies that similar strategies can be effectively applied across both cities. Future efforts should identify factors influencing these variations to tailor interventions for comprehensive dengue management and prevention. Int. J. Appl. Sci. Biotechnol. Vol 12(2): 77-83.